The Weeping Citizen: the future of Ocean in 2050 - Fabregas, Zamantha Mutuc (Nanyang Technological University, 2023)
‘The Weeping Citizen’ is a visual exploration of a speculative ocean future, where Singapore navigates efforts to reverse the catastrophic loss of 50% of all marine life on Earth due to climate change. It is motivated by the increasing urgency of the Ocean Sustainability crisis and our disconnectedness from the issue due to our lack of up-close interactions with marine life in our urban environment. This project aims to encourage Gen-Zs to become more proactive about conservation efforts in response to the ongoing Climate and Ocean Sustainability crisis and encourage inquisitiveness to become better-informed citizens. It explores the use of speculative design, utilizing sci-fi prototyping and a participatory design component to present a future scenario that synthesizes existing technologies, research, and scientific journals to contextualize a response. The project, which includes a hypothetical public web archive and experiential display, prompts the audience to reflect on their relationship with the Ocean Sustainability crisis and the impact of their actions on building a sustainable future. It aims to incite introspection and encourage the audience to consider the interconnectivity of our lives with the Ocean Sustainability crisis, the various aspects of life that would be affected, and the ways in which our actions can either help or hinder our attempts to build an ideal sustainable future. By doing so, it aims to reframe how we interact with the present, critique our existing behaviours and encourage active conversation about steps we can take from here. Keywords: Climate Design, Ocean Sustainability, Sci-fi Prototyping, Speculative, Future, Singapore, Technology